THE EFFECTS OF READING HABIT AND GRAMMAR MASTERY TOWARDS STUDENT'S READING COMPREHENSION - Zennytra Rachmativani; Supeno Supeno (Universitas Indraprasta PGRI, 2020)
The aim of this research are to find: 1) The effects of Reading Habit and Grammar Mastery jointly Towards Student’s Reading Comprehension. 2) The Effects of Reading Habit Towards Student’s Reading Comprehension. 3) TheEffects of Grammar Mastery Towards Student’s Reading Comprehension. The method used is survey method. The instruments were used multiple choice and questioner. Total samples of this research followed by 75 students with a cluster simple random technique. The result showed: 1)There are significant effects of reading habit and grammar mastery jointly towards the student’s reading comprehension. This is proved by the value of sig.0.000<0.05 and Fobserved=52.564. 2) There is a significant effect of reading habit towards student’s reading comprehension. This is proved by the This is proved by the value of sig.0.000<0.05 and tobserved=7.620. 3)There is significant effect of the grammar mastery towards student’s reading comprehension significantly. This is proved by the This is proved by the value of sig.0.000<0.05 and tobserved = 6.100.